Successful treatment of prolonged COVID-19 with Bamlanivimab in a patient with severe B-Cell aplasia due to treatment with an anti-CD20 monoclonal antibody: A case report. (2021) - Daher, Ayham; Müller, Tobias; Spiesshoefer, Jens; Dreher, Michael; Panse, Jens
Abstract: A 71-year-old female patient with B-cell depletion due to treatment with an anti-CD20 monoclonal antibody was admitted for worsening COVID-19. Overall, she had persistent viral shedding, worsening respiratory failure, and progressive pneumonia that did not improve despite dexamethasone and antibiotic therapy. After administration of bamlanivimab, a monoclonal antibody with high affinity for the receptor-binding domain of the SARS-CoV-2 spike protein, inflammatory markers rapidly decreased, SARS-CoV2 RT-PCR became negative, and the patient improved clinically and radiologically. In conclusion, we demonstrated successful treatment of prolonged COVID-19 in a patient with severe B-cell aplasia with a virus-neutralizing monoclonal antibody.